Transmission Investment in Competitive Power Systems : Decentralizing decisions in Argentina - Abdala, Manuel Angel; Chambouleyron, Andres (World Bank, Washington, DC, 2012)
Recent power outages in Argentina are largely the result of transmission problems that could be solved by more investment. Private concessionaires now operate the main and regional networks, but they are under no obligation to expand capacity. In a decentralized electricity market such as Argentina's the key to a successful transmission investment policy is coordination among the parties involved. Without coordination, an investment project in one site might affect or even disrupt power flow in another. But user coalitions are difficult to set up because of high transaction costs and in the Argentine system, because investment mechanisms do not provide a clear allocation of property rights to private investors. Investment decision making for capacity expansion is centralized, but prolonged congestion indicates that the process is not working efficiently. Argentina is searching for a decentralized solution. This note outlines the options for its high-voltage network and proposes a solution for the regional grids.